Female preference for males that have exclusively marked or invaded territories depends on male presence and its identity in the subterranean rodent Ctenomys talarum - Fanjul, Maria Sol (2018)
Territorial scent-marking provides chemical records of male competitive interactions that are available to females, who gain valuable information to assess and identify best quality partners. In this context, the solitary subterranean rodent tuco-tuco (Ctenomys talarum) offers excellent possibilities to evaluate the effects of male exclusive scent-marking of territories on female assessment. For evaluation, we used wild caught individuals of C. talarum, manipulated their scent marks within the territories in captive conditions and staged preference tests where females were able to choose between exclusive and invaded territories. The evaluation was performed in two scenarios considering the identity of the intruder scent mark: territories invaded by a strange male and territories invaded by a neighbour male. Females investigated the chemical cues deposited on the substrate of the exclusively marked territory more frequently. Next, females displayed equal interest to scent samples of both males presented in a Y-maze. Finally, when females could gain access to both individually isolated males and their scent-marked territories, they spent more time within invaded territories despite they visited them with the same frequency. Moreover, females tried to get in contact by scratching the mesh of the owner of the invaded territory more frequently. We found that females of C. talarum evaluate the homogeneity (exclusiveness) of scent marks within a male territory and then show preferences in relation to the identity of the intruder's scent –whether strange or neighbour.